2014
DOI: 10.1016/j.jmatprotec.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Hot tearing in polycrystalline Ni-based IN738LC superalloy: Influence of Zr content

Abstract: a b s t r a c tZirconium is always present in Ni base superalloys as it enhances their creep properties. In the present study, the influence of very small Zr additions, 100-400 ppm, i.e. 0.01-0.04 wt.%, on hot tearing of IN738LC superalloy is experimentally investigated using dedicated turbine blade castings. Although the Zr content remains very small, it has a strong effect on hot tearing tendency. Microstructure of hot tear in as-cast samples reveal that grain size and secondary dendrite arm spacing have no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Our observations imply that a bulk-criterion may not allow to appropriately depict near-atomic-scale processes. It is also known that Zr promotes hot cracking in nickel-based superalloys produced by casting [42][43][44][45] and AM processes [5]. Although Zr is added in the bulk composition of the investigated alloy (0.02 -0.025 at.%), APT revealed no segregation of Zr at the grain boundary.…”
Section: Hot Cracking Caused By Grain Boundary-segregation Induced LImentioning
confidence: 84%
“…Our observations imply that a bulk-criterion may not allow to appropriately depict near-atomic-scale processes. It is also known that Zr promotes hot cracking in nickel-based superalloys produced by casting [42][43][44][45] and AM processes [5]. Although Zr is added in the bulk composition of the investigated alloy (0.02 -0.025 at.%), APT revealed no segregation of Zr at the grain boundary.…”
Section: Hot Cracking Caused By Grain Boundary-segregation Induced LImentioning
confidence: 84%
“…The literature dealing with welding and weldability of Ni-based superalloys turns out to be relevant towards the effect of minor elements such as B on the hot cracking susceptibility, see e.g. [4,6,19,47].…”
Section: Presence Of Thermal Stressesmentioning
confidence: 99%
“…Several studies have recently emerged on the effects of Zr-segregation on solidification cracking in IN738LC. It is suggested that Zr-films become trapped between dendrite arms towards the grain boundaries, embrittling the grain boundary region; when stressed, cracks form similar to those of solidification cracking morphology (49,55,56).…”
Section: Defect Formation In Am Of Ni-base Superalloys: Porosity and mentioning
confidence: 99%